Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed